Occupational bullying and its impact at work "a sociological study" - ديوب نوار; يسرى زريقة (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research aimed to identify the occupational bullying problem, which is one of the main problems in the current situation due to its negative impact on the individual, the workplace, and society. This behavior is by individuals with many psychological problems like jealousy and the desire to highlight themselves above their colleagues’ successes at work, so they resort to spreading rumors and verbally assaulting them through criticism, ridicule, and screaming. One of the most essential effects of job bullying is the individual’s shame and lack of confidence. non-Self-esteem and a desire to leave his job, which reflects negatively on the work institution in terms of organization and productivity, Which Lead to huge losses. Bullying has a devastating effect on the social life of individuals subjected to bullying.